Inflammasomes in Liver Fibrosis - Alegre, Fernando; Pelegrin, Pablo; Feldstein, Ariel E. (Seminars in Liver Disease, 2017)
Cell death and inflammation are two central elements in the development of liver fibrosis. Inflammasomes are intracellular multiprotein complexes expressed in both hepatocytes and nonparenchymal cells in the liver that are key regulators of inflammation and cell fate. They respond to cellular danger signals by activating caspase 1, releasing the proinflammatory cytokines IL-1β and IL-18, as well as initiating a novel pathway of programmed cell death termed “pyroptosis.” These processes can initiate and perpetuate an abnormal wound-healing response with the principle cellular target being the activation of hepatic stellate cells. From the various inflammasomes, the NLRP3 inflammasome has been increasingly implicated in the pathogenesis of chronic inflammatory liver diseases, including nonalcoholic steatohepatitis, a disease process that is soaring and has evolved as a primary cause of liver fibrosis and need for liver transplantation. In this review, the authors highlight the growing evidence for both indirect and direct effects of inflammasomes in triggering liver fibrosis as well as potential novel targets for antifibrotic therapies.
Keywords: liver disease; fibrosis; hepatic stellate cells; cell death; danger-associated molecular patterns; pattern recognition receptors; inflammation; therapy; nonalcoholic steatohepatitis